Functionalization of decavanadate anion by coordination to cobalt(II): Binding to proteins, cytotoxicity, and water oxidation catalysis - Somasundaram, Janaki Devi; Ebrahimi, Arash; Nandan, Sreejith P; Cherevan, Alexey; Eder, Dominik; Šupolíková, Miroslava; Nováková, Eva; Gyepes, Róbert; Krivosudský, Lukáš (Journal of inorganic biochemistry, 2023)
A series of five decavanadates (V10) using a simple, one-pot synthesis, adhering to the model template: transition metal ion - decavanadate - ligands:(Hnicotinamide)2{[Co(H2O)3(nicotinamide)2]2[μ-V10O28]}.6H2O (1), {[Co(H2O)4(isonicotinamide)2]3}V10O28·4H2O (2), {[Co(H2O)4]2[Co(H2O)2(μ-pyrazinamide)2][μ-V10O28]}·4H2O (3) {[Co(H2O)4(μ-pyrazinamide)]3.V10O28}·4H2O (4), and (NH4)2{[Ni(H2O)4(2-hydroxyethylpyridine)]2}V10O28·2H2O (5) was synthesized. X-ray analysis reveals that 1 and 3 are decavanadato complexes, while 2, 4 and 5 are decavanadate complex salts. Moreover, 3 is the first example of a polymeric decavanadato complex, employing direct coordination with the metal center and the organic ligand, in toto. From the solution studies using 51V NMR spectroscopy, it was decoded that 1 and 3 stay stable in the model buffer solution and aqueous media. Binding to model proteins, cytotoxicity and water oxidation catalysis (WOC) was studied primarily for 1 and 3 and concluded that neither 1 nor 3 have an interaction with the model proteins thaumatin, lysozyme and proteinase K, because of the presence of the organic ligands in the Co(II) center, any further interplay with the proteins was blocked. Cytotoxicity studies reveal that 1 is 40% less toxic (0.05 mM) and 26% less toxic (0.1 mM) than the uncoordinated V10 with human cell lines A549 and HeLa respectively. In WOC, 1 performed superior activity, by evolving 143.37 nmol of O2 which is 700% (9-fold) increase than the uncoordinated V10.
Keywords: Ligands; vanadáty; Pyrazinamide; Humans; Catalysis; ligandy; Cytotoxicity; kobalt; lidé; Cobalt; Bioinorganic chemistry; pyrazinamid; Water oxidation catalysis; Decavanadate; Protein binding; voda; anionty; Cell viability; Vanadates; Water; katalýza; Anions